Outcomes of balloon vs basket catheter for clearance of choledocholithiasis: a systematic review and meta-analysis - Sharma, Ruchi; Sharma, Vikram; Singhal, Umang; Sanaka, Madhusudhan (Endoscopy International Open, 2022)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) is the mainstay for treatment of choledocholithiasis. It is unclear whether balloon or basket catheters are better for extraction of stones ≤ 10 mm in size. We performed a meta-analysis of studies comparing rates of complete stone extraction and adverse events after ERCP using balloon vs basket catheters for bile duct stones ≤ 10 mm in size.Methods Cochrane database, PubMed, Web of Science, and Embase were searched from inception to October 2021. Randomized control trials comparing outcomes of balloon vs basket catheter were included. Data extraction of articles was carried out by two authors using predefined inclusion criteria. Metanalysis was carried out using the Revman 5.4.1. software using a random-effects model.Results Three studies with a total of 508 patients were included in the final analysis. For common bile duct stones ≤ 10 mm, balloon catheters had higher complete stone clearance rates than basket catheters (relative risk 1.1, confidence interval 1.03, 1.18, P = 0.006). Heterogeneity among studies was low (Tau2  = 0.0; P = 0.47, I2  = 0 %). There was no difference in the rate of complications.Conclusions Meta-analysis of three studies indicates that balloon catheters have a higher success rate compared to basket catheters for complete stone extraction for choledocholithiasis ≤ 10 mm with no significant difference in the rate of complications.